Review of Learning Styles on Student with Self-Regulated Learning - M. Nur Ghufron; Rini Risnawita (ANIMA Indonesian Psychological Journal, 2013)
The aim of this study was to test the theoretical model of the effects of field-dependent and field- independent learning styles on students with self-regulated learning. The subjects of this study were students of Faculty of Education in Islamic Studies at Islamic State College in Kudus. The samples (N = 239) were collected using simple random sampling method where questionnaires were completed in the form of scales. The data was analyzed using SEM. The results showed that the proposed model fit the data (p = .037, GFI = .951, AGFI = 923, TLI = .985, and RMSEA = .037). The field-dependent learning style had significant negative effects on the three learning components of self-regulated learning (motivation, meta-cognition and behavior); while the field-independent learning style had significant positive effects on the three learning components of self-regulated learning (motivation, meta-cognition and behavior). Penelitian ini bertujuan untuk menguji model teoretik tentang pengaruh tipe gaya belajar field- dependent dan field independence terhadap belajar berdasar regulasi diri mahasiswa. Populasi dalam penelitian ini adalah seluruh mahasiswa program studi Pendidikan Agama Islam (PAI), Jurusan Tarbiyah, Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus. Sampel penelitian ini berjumlah 239 yang diambil melalui tehnik pengambilan sampel simple random sampling. Adapun teknik pengumpulan data yang digunakan dalam penelitian ini adalah kuesioner dalam bentuk skala. Data dianalisis dengan menggunakan Model Persamaan Struktural atau Structural Equation Modeling (SEM). Hasil penelitian menunjukkan bahwa, model yang dirancang dalam penelitian ini sesuai atau layak (p = .037, GFI = .951, AGFI = 923, TLI = .985 dan RMSEA = .037). Gaya belajar field-dependent berpengaruh signifikan secara negatif terhadap tiga komponen belajar berdasarkan regulasi diri yaitu motivasi, meta-kognisi dan perilaku. Sementara gaya belajar field independence berpengaruh signifikan secara positif terhadap tiga komponen belajar berdasarkan regulasi diri yaitu motivasi, meta-kognisi dan perilaku.